Clearing the Heart: Islamic Psychotherapy in Everyday Life - Faridatul Jannah; Desi Endang Maisuri; Fitri Inayah (Feelings: Journal of Counseling and Psychology, 2026)
Mental health is a crucial aspect of human life that is receiving increasing attention, especially amidst the pressures of modern life. In Islamic tradition, the concepts of peace of mind and purification of the heart have long been integral to religious teachings. This article discusses Islamic psychotherapy as an alternative approach that integrates Islamic spiritual values ​​into the psychological healing process. This research employed a qualitative method with a literature review approach, with data obtained from the Quran, hadith, classical Islamic literature, and modern psychology books and journals. The study results indicate that worship practices such as dhikr (remembrance of God), prayer, and attitudes such as patience, trust (relief), and sincerity (ikhlas) have a therapeutic effect in maintaining emotional stability and purifying the heart. Islamic psychotherapy functions not only as a form of healing but also as a preventative measure for maintaining ongoing mental health. By restoring the orientation of life to Allah SWT, individuals can achieve inner peace and a deeper meaning in life. This article is expected to contribute to strengthening the importance of integrating religion and psychology in the context of mental healing, especially for Muslims.